Romania. The National Tourism Office Magazine (Confluenţe Bibliologice, 2021)
Most of the serial publications, from the Collection of Rare Documents of USARB Scientific Library, were received as a donation from the Cultural Association Pro Basarabia and Bucovina”, Galati Branch library, secretary Radu Motoc. These documents, carefully collected by collectors, represent bibliophile and historical rarities and constitute a real treasure for the Balti Library. The article addresses the image of Romania through tourism, the importance of tourism objectives in Romania, reflected in the Journal of National Tourism Office.
Keywords: periodicals